Case report: Multiple facial trichoepitheliomas caused by p.Val835SerfsTer52 variant of CYLD gene - Gaydina, Tatiana A.; Patsap, Olga I.; Buianova, Anastasiia A. (Frontiers in Medicine, 2024)
Summary Brooke–Spiegler syndrome (BSS) is an autosomal dominant disease associated with the CYLD gene, which manifests itself as multiple benign skin tumors. We presented a young female patient with a previously undescribed heterozygous de novo mutation c.2501dupC (p.Val835SerfsTer52) of the CYLD gene. The nucleotide sequence variant was detected by clinical exome sequencing and validated by Sanger sequencing in her parents and sister. A histological examination of the elements identified multiple trichoepitheliomas. Radical removal of the largest formations of the facial skin was performed under local infiltration anesthesia with wound treatment with a CO2 laser in a pulsed-periodic mode. Nevertheless, new formations began to appear on the patient’s facial skin of the forehead, upper eyelids, nasolabial triangle, prone to growth and requiring removal. Domain modeling of the mutant protein proved its conformational difference from the wild type, as well as altered physicochemical properties. Conclusion The new CYLD gene variant p.Val835SerfsTer52 causes the development of multiple familial trichoepitheliomas in BSS and confirms the hypothesis of the association of this gene variant with loss-of-function mutations. We have verified that removing multiple trichoepitheliomas simultaneously with a CO2 laser does not impede the pathological process. Therefore, hopes are placed on targeted therapy, which is currently not developed for this disease.